Bibliometrinės užklausos kaip bibliotekos darbo dalis - (:unkn) unknown (My University, 2011)
The article discusses some services offered by libraries of several countries, such as Australia, Ireland, Germany, England, Austria, Sweden and Norway and in particular, the information on bibliometry put on the libraries’ websites. While the services provided by all the libraries are fairly similar, the amount and deapth of the information offered to readers and methods of its presentations differ. The experience of libraries in other countries must be useful for and much needed by scientific and university libraries of Lithuania, and it is merely a question of time as to who and when will be the first to introduce similar reader services.
Bibliometric queries as part of library work
Skyriaus antraštė: Straipsniai